SCHOOL DENTAL HEALTH PROGRAM: TRAINING OF TRAINER KESEHATAN GIGI DAN MULUT PADA GURU DAN ORANG TUA SEBAGAI UPAYA MENUJU PROGRAM “ INDONESIA BEBAS KARIES 2030” - Rahman, Kurnia Hayati; paramita, Ayulistya; Sucahyo, Bambang; Revianti, Syamsulina; Pinasti, Restika Anindya; Paramita, Anisa Listya; Prameswari, Noengki; Lelyna, Nora; Handayani, Budi; Widaningsih, Widaningsih; Wedarti, Yoifah Rizka; Nilawati, Nina; Harnowo, Setyo; Prabowo, Puguh Bayu; Damaiyanti, Dian Widya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Oral and dental health among school-age children is often neglected, despite its importance in supporting their quality of life. A Training of Trainer (ToT) program on oral and dental health was conducted for teachers and parents at MI KH Ramly Surabaya to support the vision of Indonesia Free from Dental Caries 2030. This training included educational sessions and guidance on proper tooth-brushing habits using fluoride toothpaste. The results showed an improvement in participants' knowledge, with higher average post-test scores compared to pre-test scores. Additionally, there was a positive behavioral change among children in maintaining oral hygiene. Although statistical tests indicated insignificant results, the intervention had a practical impact on establishing healthy habits. Support from teachers, parents, and healthcare professionals is essential to reducing the prevalence of dental caries in the future. .